Stressful by design: Exploring health risks of ride-share work. (September 2019) - Bartel, Emma; MacEachen, Ellen; Reid-Musson, Emily; Meyer, Samantha B.; Saunders, Ron; Bigelow, Philip; Kosny, Agnieszka; Varatharajan, Sharanya
Abstract: Introduction: For-hire driving work, such as taxi driving, is characterized by long hours of sedentary behaviour, passenger assault, lack of benefits or support, and isolating working conditions that jeopardize good health. The for-hire driving industry has recently expanded to include a new group of ride-share drivers from digital platforms such as Uber and Lyft; this has substantially increased the number of people engaged in for-hire driving. However, there is very little existing research on ride-share drivers' health and safety in relation to their work, and no research on the Canadian context. Methods: This paper draws from a qualitative study consisting of in-depth interviews and focus groups with ride-share drivers and passengers, taxi drivers, taxi and ride-share managers, and other industry key informants in a large Canadian city. This paper focuses on ride-share drivers' health risks on the job. Results: This study finds that ride-share drivers face physical and mental health risks resulting from ride-sharing work that are distinct to ride-share work, as well as ones similar to taxi driving and other transportation work. We find that the nature of the work is stressful by design: ride-share drivers face regular stressors and pressures from passengers, such as to speed and drive young children without proper booster seats. They also describe weight gain and muscle pain. Conclusion: As greater numbers of passengers opt for ride-share transportation and more people take up ride-share work, understanding potential short- and long-term health implications is an important area of inquiry. Understanding the working conditions of ride-share drivers can support the development of appropriate policy and practice tools to improve ride-share drivers' health and safety. Highlights: Ride-share drivers experienced physical and emotional health risks in their work. Health risks for ride-share drivers included stress, fatigue, musculoskeletal disorders, and urinary disorders. Work conditions and ride-share 'apps' indirectly promoted poor driver health. Greater awareness and knowledge of ride-share driver health is needed. Health promotion interventions are important for driver health and public safety.